Documentary Photography And Video To Enhance The Social Impact Of Rantara 2025 Inclusive Painting Exhibition - Rizqi, Ridwan Fadilah; Rio Aditya Rakhmadila; Muhammad Dziki Alfaruq; Kristina Novi Susanti (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
Through an audio-visual approach, the author not only captures moments of the exhibition activities but conveys a deeper story of how the photos and videos captured open new views on courage, diversity and inclusion in the Rantara painting exhibition. The Rantara exhibition is a forum for friends with disabilities to have equal opportunities to exhibit and sell their works, collaborate with professional painting artists so that in the future they can confidently enter the commercial art world.  RANTARA is not just an art appreciation event, but a contemplation space that raises awareness of the importance of inclusion in art and serves as a universal communication bridge. The social impact of documentary photography and video makes every individual entitled to be heard and valued, this exhibition, as part of the MBKM Mandiri Humanitarian Project of ISI Surakarta in partnership with Hanenda Vocational House, places art as a tool to convey perspectives and life experiences. Therefore, documentary photography and video play a fundamental role in recording, disseminating and amplifying the inclusive narrative that RANTARA promotes. By utilizing the visual power of photography and documentary video, it captures authentic processes, interactions and emotions. The exhibition seeks to not only represent diversity, but also evoke empathy and understanding from a wider public, so that its social impact can be measurable and sustainable.